Reliability of the metal reservoirs with the diesel fuel in the Antarctic conditions - N. I. Bouraou; Y. G. Zukovsky; D. V. Shevchuk; O. V. Kuzko (Ukrainian Antarctic Journal, 2013)
The threats and risks were investigated which faced during prolonged use they are in the Antarctic on the example of the reservoir with the diesel fuel and piping system at the Ukrainian Antarctic Vernadsky Station.  It is shown that the reservoirs and pipelines are the most dangerous objects for the environment. The most dangerous effects were studied on reservoirs from the environment.  The automated complex instrumentation is  proposed to install for reliable operation of the fuel new reservoir and pipelines of the power station complex, for the operational definition of their current condition and forecast its future changes. The complex has being developed on the basis of the latest achievements in the fields of instrumentation, information systems and computer technology.